ANALISIS DAN PEMODELAN MATEMATIS KETERSEDIAAN OKSIGEN TERLARUT SEBAGAI PARAMETER KUALITAS AIR DALAM SISTEM BUDIDAYA IKAN NILA (OREOCHROMIS NILOTICUS) DAN TANAMAN GENJER (LIMNOCHARIS FLAVA) DI DALAM EMBER (BUDIKDAMBER) DENGAN KEPADATAN POPULASI YANG BERBEDA - Kusprayogo, Fitriani
Fish farming in buckets is one type of aquaponic farming system that answers the challenges during the pandemic. Water quality in the fish culture is influenced by the population density of fish. The availability of oxygen in water is relatively lower than its availability in the air and depends on solubility. Ceratophyllum demersum is an aquatic plant that produces more oxygen and consumes less oxygen. The purpose of this research is to determine the carrying capacity of the system, the availability of DO, the rate of oxygen consumption, and a mathematical equation that describes the availability of DO in the system. This research lasted for 28 days and used tilapia fish aged 45 days and genjer aged 12 days after seeding. The results showed that the carrying capacity of the fish culture in the bucket system is less able to support the life of tilapia (Oreochromis niloticus) based on the availability of DO in the system. The average DO concentration of the fish culture in the bucket system during observations in the morning (8:00), afternoon (12:00), and afternoon (18:00) respectively, namely the treatment of 3 fish 1.8; 3.8; 2.5 mg/L, treatment of 5 fish 1.3; 2.8; 1.4 mg/L, treatment of 7 fish 1.2; 2.5; 1.3 mg/L, and treatment of 9 fish 1.2; 2.1; 1.1 mg/L. The average rate of fish consumption from each treatment, including the treatment of 3 fish, 5 fish, 7 fish, and 9 fish, respectively 0.00139; 0.00111; 0.00085; 0.00108 mg/L/g body/hour and the results of statistical tests showed a significantly different effect between the rate of oxygen consumption and population density. The availability of oxygen concentration in the bucket fish farming system during the study with 3 times in the morning (8:00), afternoon (12:00), and afternoon (18:00) can be described by a 6th-degree polynomial mathematical equation with an R2 value of consecutively 0,98; 0.98; 0.99.